CHARACTERISTIC OF PROTEASE FROM CRUDE EXTRACT OF MARINE YEAST AND ITS ACTIVITY IN HYDROLIZING TRASH FISH PROTEIN - Abdul Aziz Jaziri; Mr. Sukoso; M. Firdaus (JFMR (Journal of Fisheries and Marine Research), 2017)
Marine yeast is uniceluller microorganism from group of fungi. Marine yeast was isolated from East Java Beach have potention of biotechnology in food section. Marine yeast as an agent in hydrolyzing trash fish protein to be able to increase nutrition value of amino acid. The researches of protease characteristic from marine yeast and its activity in hydrolizing protein are poorly demonstrated. Therefore, study on characteristic of protease from  marine yeast and its activity is important to overcome abundance of trash fish. The aim of this research  was to know protease characteristic of marine yeast and characteristic of trash fish protein hydrolysate. This study used exploration method. The result of this study were the protease characteristic from crude extraction of marine yeast showed that protein concentration value is 22.17 mg/L, protease activity is 21.50 mU/min/mL, Vmaks is 37.25 mmol/L/min and KM value is 2.3 × 103 mM. While the characterstic of trash fish protein hydrolysate is 22.35%, the total of amino acids is 1.32% and the molecular mass is 14.39 kDa. In addition, this study showed that protease activity from marine yeast extraction had low activity because protease extracted from marine yeast is crude extract. Keywords: marine yeast, protease, hydrolysis, trash fish protein